Assesment of attractiveness of Istanbul for foreign investment - Gülden Demet Oruç; Ferhan Gezici; Ebru Kerimoğlu (European Regional Science Association (ERSA), 2012)
Istanbul metropolitan region is the economic heart of Turkey, which is generally listed among the emerging economies of the last decade. Although compared to other European regions foreign capital and investment are underrepresented in Istanbul, economic growth and the stability of Turkey in the last decade made of Istanbul the most developed region and the most attractive for foreign capital not only in Turkey but also in a wider regional context, with a notable effect on the attraction of human flows into the city. Istanbul has been one of the main destinations of internal migration in Turkey, since the beginning of industrialization process in the 1960s. The main motivation for the people who migrate (especially the unskilled) has been traditionally related to employment and emancipation. However, the recent changes of the Turkish economy – and the policy objectives that are attached to it – are transforming Istanbul into a new hub for other types of migration, like high skilled foreign workers from OECD countries and other forms of short-to-medium term mobilities, which overlap and interact with the traditional opportunity-driven migration. In this paper we will especially focus on Istanbul's current situation and proactive strategy of attracting foreign investments and companies, looking for factors that may explain the performance of Istanbul in terms of flows attracted. First, we perform an assessment of the situation of Istanbul in terms of attractiveness. On this basis, we develop an in-depth profile of Istanbul as an attractive city characterized by an increased capacity to attract specific flows. The profile of the region is analyzed through the existing position, potentials and obstacles. In the second part, we address the questions as the main factors that explain the attraction of foreign investors and labor to Istanbul, the characteristics of specific successful mobilization strategies, the expectations concerning the future development of Istanbul's attractiveness, using qualitative analysis obtained though face-to face interviews with stakeholders.
Keywords: J11O19R28R58; 330; Attractiveness; foreign investment; Istanbul